Adiposity, related biomarkers, and type 2 diabetes after gestational diabetes: The Diabetes Prevention Program. Issue 1 (18th November 2021) - Wander, Pandora L.; Christophi, Costas A.; Araneta, Maria Rosario G.; Boyko, Edward J.; Enquobahrie, Daniel A.; Dabelea, Dana; Goldberg, Ronald B.; Kahn, Steven E.; Kim, Catherine; Pi‐Sunyer, Xavier; Knowler, William C.
Abstract: Objective: This study investigated associations of adiposity and adiposity‐related biomarkers with incident type 2 diabetes (T2D) among parous women. Methods: Among women in the Diabetes Prevention Program (DPP) who reported a previous live birth, circulating biomarkers (leptin, adiponectin, sex hormone‐binding globulin, and alanine aminotransferase; n = 1, 711) were measured at enrollment (average: 12 years post partum). Visceral (VAT) and subcutaneous adipose tissue areas at the L2‐L3 region and the L3‐L4 region were quantified by computed tomography ( n = 477). Overall and stratified (by history of gestational diabetes mellitus [GDM]) adjusted Cox proportional hazards models were fit. Results: Alanine aminotransferase, L2‐L3 VAT, and L3‐L4 VAT were positively associated (hazard ratio [HR] for 1‐SD increases: 1.073, p = 0.024; 1.251, p = 0.009; 1.272, p = 0.004, respectively), and adiponectin concentration was inversely associated with T2D (HR 0.762, p < 0.001). Whereas leptin concentration was not associated with T2D overall, in GDM‐stratified models, a 1‐SD higher leptin was positively associated with risk of T2D in women without GDM (HR: 1.126, p = 0.016) and inversely in women with a history of GDM (HR: 0.776, p = 0.013, interaction p = 0.002). Conclusions: Among parous women, alanine aminotransferase and VAT are positively associated with incident T2D, whereas adiponectin is inversely associated. Leptin is associated with higher risk of T2D in women with a history of GDM but a lower risk in women without a history of GDM.